Photographs of Street Signs with Mistakes as an Educational Resource (with Examples from Berehove in Western Ukraine) - Shylov, Volodymyr (Slavistica Vilnensis, 2025)
The city of Berehove is located in the Zakarpattia (Transcarpathia) region (Oblast) of Ukraine, near the border with Hungary. A significant part of the local population is Hungarian-speaking; that is why, for the more than 150000 Transcarpathian Hungarians, Berehove serves as an unofficial cultural center. At the time of the main data collection (2019–2021), street signs in the city could be found in Ukrainian, Hungarian, Russian, English, and other languages. Such a highly multilingual urban environment gives rise to various types of mistakes, as not all residents are fluent in the common languages. The Hungarian minority in Transcarpathia faces difficulties in learning the Ukrainian language, as it was not compulsory during the Soviet period. The compact settlement of the Hungarian population in Transcarpathia means that they may have very limited contact with speakers of Slavic languages. In addition, the grammar of Ukrainian and Russian is difficult for Hungarians. The article focuses on errors in Ukrainian and Russian texts, but also provides some examples of street signs in Hungarian and English that deviate from linguistic norms. This study proposes an approach that involves students in the joint identification and analysis of such errors in street signs. The inclusion of such exercises in the educational process can help children develop the habit of carefully observing their linguistic environment and critically evaluating their own speech.